Weaning of infants from non invasive ventilation - Gizzi, C.; Massenzi, L.; Pattumelli, M. G.; Moretti, C.; Agostino, R. (Acta Biomedica Atenei Parmensis, 2014)
Non invasive ventilation (NIV) is commonly used to treat RDS in preterm infants. Although less risky than invasive ventilation, NIV has some potential side effects and appropriate weaning is therefore desirable. However, criteria for the definition of stability prior to attempting NIV weaning as well as the best weaning strategies need to be more investigated. The aim of this review is to identify criteria and interventions that can facilitate correct weaning from NIV.